Syncretism in Nordic folk medicine: critical periods during pregnancy - Lily Weiser-Aall (Scripta Instituti Donneriani Aboensis, 1969)
This article explores the traditions concerning the critical periods during pregnancy when the foetus is exposed to the risk of suffering serious injuries. There is a good deal of such traditions in more recent Nordic and European folklore. But these popular conceptions have merely been recorded without having ever been investigated as to their provenance. In studies of various details in recent Nordic tradition it is possible to establish a striking correspondence between, on the one hand, folk tradition and, on the other, learned publications and popular accounts in books on healing and midwifery. This actualizes an interest to investigate the beliefs about critical periods by a comparison with the theories of the learned tradition.